The body of power, the body of memory. Issue 1 (2nd January 2017) - Schepartz, Lynne A.
ABSTRACT: Bioarchaeology is a relatively new and dynamic area of anthropological research, having grown out of the New Archaeology's emphasis on understanding formation processes within a broader anthropological/behavioral context. Current bioarchaeological research is increasingly focused on questions of identity and social roles from the perspectives of agency and embodiment and with an emphasis on contextual interpretation, as illustrated by the edited volumes discussed in this review. The relevance of this bioarchaeology research extends to other areas of anthropological enquiry, especially when considering the importance of the body in power and identity construction in contemporary societies.